2013
DOI: 10.1007/s12022-013-9270-y
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Mediators of Cell Invasiveness, Motility, and Migration in the Pathogenesis of Silent Corticotroph Adenomas

Abstract: Silent corticotroph adenomas (SCAs) represent a distinct subset of clinically non-functioning pituitary adenomas. There are two variants of SCA; type I are densely granulated basophilic tumors and type II are sparsely granulated and chromophobic tumors. SCAs are known to be aggressive than the more common non-functioning gonadotroph adenomas (NFGAs). Cell-matrix interactions play an important role in the pathogenesis of pituitary adenomas. In this study, we compared 19 SCAs and 50 NFGAs with known fibroblast g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
18
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(20 citation statements)
references
References 55 publications
2
18
0
Order By: Relevance
“…One study demonstrated higher β1-integrin and osteopontin expression and lower MMP-1 and FGFR4 immunoreactivity in SCAs compared to NFAs [34]. Galectin-3, which is involved in cell growth and differentiation, cell adhesion, and tumor progression, is more abundantly expressed in CD compared to SCAs [21,43,55].…”
Section: Pathogenesismentioning
confidence: 99%
“…One study demonstrated higher β1-integrin and osteopontin expression and lower MMP-1 and FGFR4 immunoreactivity in SCAs compared to NFAs [34]. Galectin-3, which is involved in cell growth and differentiation, cell adhesion, and tumor progression, is more abundantly expressed in CD compared to SCAs [21,43,55].…”
Section: Pathogenesismentioning
confidence: 99%
“…also, when compared to other clinically silent adenomas (mainly null cell adenomas and gonadotrophs adenomas), patients younger than 30 years of age with silent corticotroph adenomas more often have multiple recurrences (>2) and late recurrences (more than five years after initial resection) (15). It has been suggested that interactions between tumour cells and extracellular matrix may be one of the mechanisms leading to distinct behaviour by these pituitary adenomas; it may be that osteopontin plays a role in the invasiveness of SCas, whereas MMP-1 is more frequently expressed in gonadotroph adenomas (16).…”
Section: A Clinically Non-functioning Pituitary Adenomasmentioning
confidence: 99%
“…corticotroph adenomas are classified as type 1 (Figure 2a) and type 2 SCas, respectively. It has been shown that type 2 SCas have a higher expression profile of factors regulating tumor cell invasion/ migration and proliferation, such as MMP-1, β1-integrin, and FGFr4, compared with type I SCas 16 . Corticotroph adenomas with Crooke's hyaline change, also known as "Crooke cell adenomas", have also been associated with aggressive behaviour (19,20).…”
mentioning
confidence: 99%
“…Harada et al (24) have reported telomerase activity by using Southern blotting and reverse transcriptase-chain reaction in a pituitary carcinoma evolving in a background of an initially telomerase-negative PrL-producing benign aggressive manner by local invasion through surrounding tissues, recurrences, and resistance to medical therapies (4,8). Many studies have aimed to discover a significant predictor of an aggressive clinical course in pituitary adenomas (1,4,(9)(10)(11)(12). Telomerase reverse transcriptase (TErT), a catalytic subunit of telomerase that includes an rnA component (TErC), therewithal maintains the telomere homeostasis and chromosomal integrity (15).…”
Section: Comparisons Of Cytoplasmic Tert Expression With Clinicopathomentioning
confidence: 99%
“…Thus, the WHO classification defined these tumours as invasive pituitary adenomas with increased mitotic activity, a ki-67 proliferation index of >3%, and extensive p53 immune staining, namely, 'atypical adenomas'. To predict the behaviour of these tumours, many studies have been performed by investigating various markers related to chromosomal alterations, micrornAs (mirnAs), proliferation markers, oncogenes, tumour suppressor genes, angiogenesis, cell adhesion, growth factors, and their receptors (1,4,(9)(10)(11)(12). Such studies show that none of these markers may predict the behaviour of these tumours alone, but combinations of fibroblast growth factor receptor 4 (FGFr4), matrix metalloproteinases (MMPs), particularly MMP2 and MMP9, ki-67, p53, pituitary tumour transforming gene (PTTG), and deletions in chromosome 11p seem to have benefits for predicting the aggressiveness of pituitary adenomas (1).…”
Section: Introductionmentioning
confidence: 99%